Mixed reality and human-robot interaction - Wang, Xiangyu , 1979- (Intelligent Systems, Control and Automation: Science and Engineering, 2011)
Written by a blend of leading researchers from academia and industry, this volume provides a comprehensive reference to MR in Human-Robot Interaction. The contributions present the current research topics in this field, technological advancements, and working examples